PENGEMBANGAN E-MODUL BERBASIS PjBL DENGAN PENDEKATAN GAMIFIKASI TERHADAP KEMAMPUAN LITERASI SAINS DAN LITERASIDIGITAL SISWA - Fani Febriana; Riswanto; Eko Prihandono (Universitas Muhammadiyah Metro, 2025)
The condition of physics learning at Kesuma Bhakti High School shows that student activity still varies, and the use of technology in learning is not yet optimal. In addition, the availability of books at school is actually adequate, but the limitations of the lending system, which only allows use for a certain period of time, means that students cannot always access books at home. This condition has an impact on the suboptimal opportunities for independent learning outside of school. This problem has resulted in low science literacy among students due to the use of textbooks, suboptimal independent learning, difficulties in understanding physics concepts, and limited digital literacy due to the lack of utilization of technology-based devices. However, this condition is also supported by students' interest in physics and their ownership of mobile phones, which can be used as alternative learning media. In addition, students' interest in learning increases when learning is packaged with interactive and fun game elements. Based on these conditions, this study was conducted to assess the feasibility of PjBL-based e-modules with a gamification approach and to determine students' science and digital literacy skills after using the e-modules. The study was conducted using an R&D approach with the ADDIE model. Data were collected through expert validation, science literacy tests, digital literacy questionnaires, and teacher and student response questionnaires. The validation results showed a percentage of 94.5% (very feasible category). The application of the e-module resulted in an increase in science literacy skills with an N-gain of 0.62 (moderate category) and digital literacy of 0.63 (moderate category). In addition, teacher response reached 100% (very good) and student response 79.35% (good). These findings confirm that PjBL-based e-modules with a gamification approach are not only feasible but also capable of addressing physics learning problems related to low science and digital literacy among students.